Recent Advances in the Role of Discoidin Domain Receptor Tyrosine Kinase 1 and Discoidin Domain Receptor Tyrosine Kinase 2 in Breast and Ovarian Cancer - Chen, Li; Kong, Xiangyi; Fang, Yi; Paunikar, Shishir; Wang, Xiangyu; Brown, James A. L.; Bourke, Emer; Li, Xingrui; Wang, Jing (Frontiers in Cell and Developmental Biology, 2021)
Discoidin domain receptor tyrosine kinases (DDRs) are a class of receptor tyrosine kinases (RTKs), and their dysregulation is associated with multiple diseases (including cancer, chronic inflammatory conditions, and fibrosis). The DDR family members (DDR1a-e and DDR2) are widely expressed, with predominant expression of DDR1 in epithelial cells and DDR2 in mesenchymal cells. Structurally, DDRs consist of three regions (an extracellular ligand binding domain, a transmembrane domain, and an intracellular region containing a kinase domain), with their kinase activity induced by receptor-specific ligand binding. Collagen binding to DDRs stimulates DDR phosphorylation activating kinase activity, signaling to MAPK, integrin, TGF-β, insulin receptor, and Notch signaling pathways. Abnormal DDR expression is detected in a range of solid tumors (including breast, ovarian, cervical liver, gastric, colorectal, lung, and brain). During tumorigenesis, abnormal activation of DDRs leads to invasion and metastasis, via dysregulation of cell adhesion, migration, proliferation, secretion of cytokines, and extracellular matrix remodeling. Differential expression or mutation of DDRs correlates with pathological classification, clinical characteristics, treatment response, and prognosis. Here, we discuss the discovery, structural characteristics, organizational distribution, and DDR-dependent signaling. Importantly, we highlight the key role of DDRs in the development and progression of breast and ovarian cancer.